Comparison of Efficiency and Cost of Methods for Conditioning of Slurries of Steam-Pretreated Softwood - Ilanidis, Dimitrios; Stagge, Stefan; Alriksson, Björn; Cavka, Adnan; Jönsson, Leif J. (Frontiers in Energy Research, 2021)
Inhibitors formed during pretreatment impair lignocellulose bioconversion by making enzymatic saccharification and microbial fermentation less efficient, but conditioning of slurries and hydrolysates can improve fermentability and sometimes also enzymatic digestibility. Conditioning of pretreated softwood using four industrial reducing agents (sodium sulfite, sodium dithionite, sodium borohydride, and hydrogen) was compared with standard methods, such as overliming and treatment with activated charcoal. A dosage of approx. 1 mM sulfur oxyanion (sulfite or dithionite) per percent water-insoluble solids (WIS) in the slurry was found to result in good fermentability. Treatment of 10–20% WIS slurries with 15 mM sulfur oxyanion under mild reaction conditions (23°C, pH 5.5) resulted in sulfonation of the solid phase and saccharification improvements of 18–24% for dithionite and 13–16% for sulfite. Among the different conditioning methods studied, treatment of slurries with sodium sulfite was superior with respect to cost-efficient improvement of fermentability. Treatments of slurry or pretreatment liquid with 15 mM sulfite or dithionite resulted in 58–76% reduction of the content of formaldehyde. The comparison indicates that conditioning of pretreated biomass using sulfur oxyanions warrants further attention.